An Analysis of Marine Tourism Object Development as A Contribution Towards Community Welfare in Lamongan District - Yanto, M.; Efendi, Yuhronur (Journal of International Conference Proceedings, 2020)
The development of marine tourism area is one of the forms of tourist management areas which strive and aim to provide benefits, especially for the protection, preservation and utilization of tourism potential and environmental services of natural resources, specifically in coastal areas. In the development of marine tourism areas, it is necessary to determine the exact location of each region so that there is no imbalance between the residential growth with marine tourism areas which being managed and utilized for recreational activities. The welfare of the community can be seen from various components that can describe whether the community is already in a prosperous life or not. Visible components include the state of housing in which they live, the level of education, and health. The role of the tourism sector, especially marine tourism in Lamongan City, can be seen from its contribution to gross regional domestic product (PDRB) in terms of labor absorption and business opportunities. The increasing contribution of the trade sector, hotels, and restaurants donated to gross regional domestic product (PDRB), are an overview of the role of the tourism sector. The purpose of this study can be described as follows: 1). To find out how extent the influence of marine tourism development on community welfare in Lamongan District. 2). To find out how extent the influence of marine tourism development on GDRP growth in Lamongan District. For the method of the study, primary data collection was conducted by interview and observation, while secondary data was obtained from Lamongan Tourism Office as well as literature study, who’s the data is in the form of general conditions and the number of visitors in the area.